GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 134 species occurrences available in GBIF matching the query: TaxonKey: Ferocactus pilosus (Galeotti) Werderm.. The dataset includes 134 records from 20 constituent datasets: 53 records from iNaturalist Research-grade Observations. 5 records from UCBG TAPIR Provider. 6 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 2 records from Jardin botanique de Montréal (JBM). 3 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 12 records from Tropicos Specimen Data. 1 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 1 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 1 records from Flora y vegetación de la Sierra de San Carlos en el municipio de San Nicolás, Tamaulipas. 1 records from Botanical Garden Collection. 2 records from Herbarium de Geo. B. Hinton, México. 4 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 1 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Sukkulentensammlung Zürich. 4 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from SBT-Living. 1 records from Botany (UPS). 7 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 25 records from SysTax - Botanical Gardens. 1 records from CAS Botany (BOT). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences